2000
DOI: 10.1002/1099-1166(200011)15:11<1034::aid-gps231>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Dementia with Lewy bodies: findings from an international multicentre study

Abstract: Objectives. To describe the baseline demographic, neuropsychiatric and neurological data of a large selected clinical sample of patients with dementia with Lewy Bodies (DLB) from an international multicentre trial with rivastigmine. To examine the usefulness of the Consensus Criteria for the diagnosis of DLB in different countries. Methods. Seventeen centres from Spain, the UK and Italy recruited patients diagnosed clinically as probable DLB according to recent Consensus Criteria (McKeith et al., 1996). A stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
21
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 35 publications
9
21
0
1
Order By: Relevance
“…However, DLB patients with more severe visuospatial deficits carried less NFT burden, suggesting that a process related to the formation of Lewy bodies rather than AD pathology contributed to their clinical syndrome. These results also bolster the contention that the DLB phenotype is strongest in individuals who have minimal NFT (Cormack et al, 2004; Del Ser et al, 2000; McKeith et al, 2005; Merdes et al, 2003). …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, DLB patients with more severe visuospatial deficits carried less NFT burden, suggesting that a process related to the formation of Lewy bodies rather than AD pathology contributed to their clinical syndrome. These results also bolster the contention that the DLB phenotype is strongest in individuals who have minimal NFT (Cormack et al, 2004; Del Ser et al, 2000; McKeith et al, 2005; Merdes et al, 2003). …”
Section: Discussionsupporting
confidence: 75%
“…In addition to the hallmark α-synuclein inclusions (i.e., Lewy bodies) in neocortical, limbic, and subcortical brain regions, the majority of patients with DLB also develop concomitant neurofibrillary tangles (NFT) and neuritic plaques (NP) in the same limbic and neocortical distribution as in AD (Armstrong, Cairns, & Lantos, 1998; Hansen et al, 1990), although fewer NFT are typically found in DLB (Gelb, Oliver, & Gilman, 1999; Hansen et al, 1990). The clinical phenotype associated with DLB appears to be weaker in patients who have extensive NFT (Cormack, Aarsland, Ballard, & Tovee, 2004; Del Ser et al, 2000; Merdes et al, 2003). In patients with Lewy bodies, a clinical syndrome that is strongly characteristic of DLB is associated with greater Lewy body burden (Cormack et al, 2004; Harding, Broe, & Halliday, 2002) and neurochemical disruption (Ballard et al, 2000; Ballard et al, 2002; Perry et al, 1991; Teaktong et al, 2005).…”
mentioning
confidence: 99%
“…In our study, this association was confirmed to be much more prominent and statistically significant in females. Studies examining the role of Lewy body pathology on psychosis have focused on subjects with dementia with Lewy bodies, where psychosis, particularly visual hallucinations, and to a lesser degree delusions are characteristic (37, 38). A study by Engelborghs and colleagues on 11 subjects with dementia with Lewy bodies showed a relationship between ε4 allele and delusions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Motor features mediated by non‐dopaminergic systems have been associated with incident dementia. Parkinsonism is also common in DLB, occurring at some point during the course of the illness in 75 to 80% cases 17–19. There are no prospective clinicopathological studies available to clarify whether the extrapyramidal features of DLB differ from those of PD.…”
mentioning
confidence: 99%